Response of biathlete organism to training load in ATC 2011/2012 - Paugschová, B.; Hasilla, T.; Murinová, A.; Ondrácek, J.; Pavlovic, R. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2013)
In the paper, we have, by monitoring ANT cardiac rate shift and ANT speed, determined the relationship between volume and intensity of training. T.H. always after completion of at least one-week training at the aerobic intensity in conjunction with training above ANT, which he usually performed as a complex training, has recorded increase in performance. This assumption is based on the results, which he had achieved at an international race. On the contrary, at the pace of middle intensity a decrease in performance occurred, especially in shorter races. The training methods recommended to T.H. - excluding the middle training zone - have been confirmed. We recommend including the utilization of the medium intensity into the preparation only within complex training